Diseño de un centro educativo infantil aplicando arquitectura pasiva en Urbanización Villa Bonita, Guayaquil - Hernández Peñafiel, Aurora Alejandra (2024)
This work presents a proposal for the design of a children's educational center in the Villa Bonita urbanization, located in Guayaquil, and focuses on the implementation of passive architecture principles. Passive architecture maximizes the interior comfort of buildings through strategies that enhance the use of natural resources, thus reducing dependence on ratifying systems. In an environment like Guayaquil, with a warm-humid climate, this is essential to create educational spaces that are both functional and sustainable. The application and integration of passive architecture strategies in the design of this educational center not only responds to an environmental need, but also has long-term economic benefits thanks to energy savings.....